ZAKAT OPTIMIZING STRATEGY THROUGH VOLUNTEERISM (IAIN Tulungagung, 2020)
The aim of this research is to optimize zakat potential in Indonesia both collection and distribution. One of the efforts to optimize is by involving millennial generation in the collection of zakat, their management and yields and sustainability. The current number of millennials is the highest among other generations. Millennial generation involvement can be in the form of volunteerism. The development of the voluntary movement in Indonesia is increasingly widespread with various activities such as social services, training, education, public health, environment, conservation, culture, arts and culture, tourism and others. The Zakat Institution must have a model of good voluntary movement management so it can assist the process of collecting, managing and distributing Zakat. The more people involved in zakat optimizing, more people will have understanding and awareness of the important role and benefits of zakat for Indonesia.